As m?scaras de chifre do carnaval de Maragogipe-BA: carnaval, cultura e patrim?nio - Seixas, Eder Santos (2025)
This dissertation investigates the horned masks of the Carnival of Maragogipe, in the state of Bahia, as symbolic expressions of the local popular culture. The research is grounded in both personal and community experiences, aiming to understand the aesthetic, historical, and identity-based meanings of these masks, which stand out for their visual impact and strong presence in the streets during the festivities. Based on theorists such as Canclini (1995, 2003), Paulo Miguez (2004), Bakhtin (1987), Tylor (2014), Arantes (1990), among others, the study proposes an interdisciplinary analysis based on three main axes: culture, carnival, and heritage. The methodological approach is qualitative, employing bibliographic, documentary, and field research, including photographic records. The dissertation is structured in three chapters: the first introduces the city of Maragogipe and its cultural narratives; the second discusses carnival in both universal and localized dimensions; and the third analyzes the horned masks as cultural and heritage elements. In conclusion, the study presents the findings and reaffirms the importance of valuing the cultural traditions of the Rec?ncavo Baiano, with emphasis on the role of the horned masks as living symbols of Maragogipe's identity.